Kelayakan LKPD Matematika Berbasis STEAM-PjBL: Tinjauan Validitas dan Praktikalitas - Mardiati Mardiati; Misliyana Misliyana; Khairina Afni (Jambura Journal of Mathematics Education, 2025)
This study aims to develop a STEAM–Project Based Learning (PjBL) student worksheet integrated with the Pancasila Student Profile Strengthening Project (P5) on the topic of polyhedrons for junior high school students. The research employed a Research and Development (RD) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 35 eighth-grade students of SMP IT SDML and one mathematics teacher in the 2024/2025 academic year. The research instruments included material expert validation sheets, media expert validation sheets, and student response questionnaires. The validation results showed that the worksheet obtained a score of 89.6% from material experts and 91.7% from media experts, both categorized as very valid. The practicality test based on responses from 34 students resulted in a percentage of 91.18%, categorized as very practical. These findings indicate that the developed STEAM–PjBL worksheet integrated with P5 is feasible and practical to be used as a teaching material to support active and contextual mathematics learning.